Iron(III)-based metal-organic frameworks as visible light photocatalysts - Laurier, Katrien G M; Vermoortele, Frederik; Ameloot, Rob; De Vos, Dirk E; Hofkens, Johan; Roeffaers, Maarten B J (Journal of the American Chemical Society, 2013)
Herein, a new group of visible light photocatalysts is described. Iron(III) oxides could be promising visible light photocatalysts because of their small band gap enabling visible light excitation. However, the high electron-hole recombination rate limits the yield of highly oxidizing species. This can be overcome by reducing the particle dimensions. In this study, metal-organic frameworks (MOFs), containing Fe3-μ3-oxo clusters, are proposed as visible light photocatalysts. Their photocatalytic performance is tested and proven via the degradation of Rhodamine 6G in aqueous solution. For the first time, the remarkable photocatalytic efficiency of such Fe(III)-based MOFs under visible light illumination (350 up to 850 nm) is shown.